Legal Analysis of the IKEA Trademark Removal Dispute Case (Study of Decision Number 165 PK/Pdt.Sus/2012) - Maurend Benaya Immanuel Susanto; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Brands have an important function for their owners, especially in the era of global trade. Trademarks provide an indication of the origin and quality of the goods or services traded. Trademark owners have the exclusive right to authorize or prohibit others from using the same or similar trademarks as theirs. Indonesia uses a constitutive registration system, in which exclusive rights are given to registered marks. Trademark applicants may not register the same mark as another well-known trademark. Registered trademark must be used. Trademark cancellation is carried out when the brand has not been used for three consecutive years. In general, trademark revocation occurs when a mark is not used in trade in goods and services. If the former owner still wants the same trademark rights, he/she must apply for trademark registration and go through the entire registration procedure. If the other party applies for the mark first, the old owner can object. If this effort fails, he can submit an annulment to the Commercial Court, cassation, and review.